Gambaran Leukosit Pada Penderita Demam Typoid 1-3 Hari Di Rsu Wisata Uit Makassar - Andi Auliyah Warsyidah; Risnawati Risnawati (Jurnal Media Laboran, 2020)
Typoid fever is a systemic disease that has the characteristics of fever and abdominal pain caused by the dissemination of S. typhi or S. paratyphi.The purpose of this study was to determi ne the number of types of leukocytes in patients with 1-3 days typoid fever in UIT Makassar General Hospital in Makassar City 2019. The benefit of this research is that it can be used as input material, literature material for the community and especially for researchers. This study uses a random sampling method and is presented in the form of descriptive analysis. Based on the results of the study showed the results of the description of leukocyte counts in patients with typoid fever. The conclusion of this study was that there were 2 samples of normal leukocytes, 1 sample for leukocytes and 7 samples for decreasing numbers of leukocytes. The conclusion was that the number of leukocytes in patients with typoid fever varied in number